2003
DOI: 10.1164/rccm.200206-563oc
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasmosis after Treatment with Anti–Tumor Necrosis Factor-α Therapy

Abstract: Anti-tumor necrosis factor-alpha (TNF-alpha) antibodies are frequently used to treat inflammatory diseases. However, these drugs also have immunosuppressive effects. We report on three patients who developed disseminated histoplasmosis on therapy with TNF-alpha inhibitors. In vitro assays were used to characterize the role of these agents in host defense against Histoplasma capsulatum. Intracellular proliferation of H. capsulatum was measured in alveolar macrophages and peripheral monocytes of normal volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(95 citation statements)
references
References 25 publications
2
92
0
1
Order By: Relevance
“…9A) and the absence of anti-CD3-induced TNF-␣ production (Table I) show that the primary cellular source of TNF-␣ is the macrophage, and T cells contribute little if any to local TNF-␣ levels. Therapeutic anti-TNF-␣ treatments induced reactivation of latent H. capsulatum infection in some patients, emphasizing the role of this mediator in control of the yeast and preventing dissemination (8,10,61). The granuloma has strong Th1-type and very little Th2-type cytokine activity (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…9A) and the absence of anti-CD3-induced TNF-␣ production (Table I) show that the primary cellular source of TNF-␣ is the macrophage, and T cells contribute little if any to local TNF-␣ levels. Therapeutic anti-TNF-␣ treatments induced reactivation of latent H. capsulatum infection in some patients, emphasizing the role of this mediator in control of the yeast and preventing dissemination (8,10,61). The granuloma has strong Th1-type and very little Th2-type cytokine activity (Table I).…”
Section: Discussionmentioning
confidence: 99%
“…While the disease course is typically indolent in immunocompetent hosts, it is more likely to be severe in immunocompromised individuals such as patients with advanced HIV infection, hematologic malignancies or those receiving chemotherapy, corticosteroids or anti-TNF-a therapies. [31][32][33] A high inoculum can cause life-threatening disease in immunologically intact individuals. 34 Hence, the spectrum of disease manifestations range from asymptomatic to an acute respiratory illness with flu-like symptoms to life-threatening disseminated disease with high fever and respiratory compromise 30,31,35 The infection is acquired via inhalation of microconidia or small mycelial fragments into the terminal bronchioles and alveoli where the fungus transform into its yeast phase.…”
Section: Dendritic Cells In the Immune Responsementioning
confidence: 99%
“…Studies in animal models demonstrate that TNFα plays a critical role in defense against infections due to histoplasma, cryptococcus, coccidiodes, candida, aspergillus and pneumocystis [87][88][89]. Studies in three patients with histoplasmosis associated with INF use showed that INF interfered with the host's helper T cell response to histoplasma antigens [90].…”
Section: Mechanism Of Treatment-limiting Adverse Responsesmentioning
confidence: 99%